P656 Malnutrition rates are highest in pre-surgical Crohn's disease when compared with active CD, CD in remission and UC in remission. (25th January 2019) - Sandall, A; Patel, K; Shah, P; O'Hanlon, D; Smith, S; Darakhshan, A; Irving, P; Sanderson, J; Lomer, M
Abstract: Background: Malnutrition occurs in 20–85% of patients with inflammatory bowel disease (IBD) depending on the nutrition assessment criteria and disease activity. Patients with Crohn's disease (CD) and malnutrition awaiting surgery are at increased risk of post-operative complications compared with patients without malnutrition. This study aimed to assess whether there were any differences in nutrition status between pre-surgical CD, active CD, CD in remission and ulcerative colitis (UC) in remission. Methods: Patients with pre-surgical CD, active CD, CD in remission and UC in remission were recruited from a UK hospital IBD unit. Anthropometric measurements were weight, height, body mass index (BMI), waist circumference (WC), mid-upper arm circumference (MAC), triceps skinfold (TSF) and mid-arm muscle circumference (MAMC). Bioelectrical impedance analysis (BIA) determined fat mass (FM) and fat-free mass (FFM). Muscle strength was assessed using hand-grip strength (HGS). Malnutrition was categorised as ≤5th percentile of the age- and gender-specific population reference range for MAC, MAMC and TSF and < 85% of the age- and gender-specific population reference range for HGS. Comparisons between groups were made using one-way ANOVA for continuous data and chi-squared for categorical data with significance set at p < 0.05. For significant results, post hoc analysis identified which groups differed. Results: A total of 121 patients with IBD were assessed. Malnutrition was identified in 21 (17%) patients using MAC, 6 (5%) patients using TSF, 39 (32%) patients using MAMC and 55 (46%) patients using HGS. No differences between groups were identified for weight, height, WC, FM, FFM, TSF and MAMC. Differences between groups were found for BMI, MAC and HGS (Table 1). Post hoc analysis showed where the differences between groups were: BMI (pre-surgical CD vs. CD in remission, p = 0.04), MAC (presurgical CD vs. CD in remission, p = 0.003; presurgical vs. UC in remission, p = 0.033) and HGS (presurgical CD vs. CD in remission, p = 0.014; presurgical vs. UC in remission, p < 0.001). Conclusions: Across IBD phenotypes and disease activity groups, nutrition status is most depleted in pre-surgical CD patients. Nevertheless, clinically significant rates of malnutrition also occur during active disease and in remission. These data may help healthcare services prioritise dietetic provision to IBD patients, specifically for pre-surgical CD patients.